(untitled) (Academia Journal of Medicine, 2019)
Background: The prevalence of end-stage renal disease (ESRD) requiring renal replacement therapy is rising steadily in developed and developing countries. Currently, continuous ambulatory peritoneal dialysis (CAPD) and in-center hemodialysis (HD) are the two major modes of dialysis used to treat ESRD. Only 8% of PD patients are initiated on PD directly, 92% are shifted from HD There are several approaches to measuring peritoneal membrane function like peritoneal equilibration test (PET), the standard permeability analysis (SPA). Successful treatment with PD encompasses several important quality targets like Patient survival, Technique survival, Quality of life, Nutrition status. Complications includes Catheter malfunction, Exit site infection, Peritonitis, Fluid leaks. In this observational study of clinical profile of CAPD patients 40 patients were taken. Of the 40 patients included in study 72.5% were male and 27.5% were female. Various factors for preference of CAPD are remote places, expenditure (35%), cardiovascular morbidity (25%). The observations are out of 52 % had well maintained nutrition, KT/V score ranges from 1.2 to 7 with mean (SD) 3.88 ± 1.59, only 22.5% have peritonitis and catheter exit site infections. None had catheter removal. All our outcome (such as correction of anemia, nutritional status, clinical well-being, absence of edema) and biochemical parameters (for e.g. Peritoneal Equilibrium Test, weekly KT/V) will used to knowing the adequacy which is consistent to results of various national and international studies.